( 6 − 7 i ) ( − 8 + 3 i )
First FOIL:
( 6 − 7 i ) ( − 8 + 3 i ) = -48 + 18i + 56i -21i^2
Combine like terms
= -48 + 74i -21i^2
Convert i^2 = -1
= -48 + 74i -21(-1)
And simplify
= -48 + 74i + 21
= -27 + 74i
<span><span><span>−<span>36n</span></span>−75</span>=<span>n−65</span></span><span>−36n−75−n</span><span>=</span><span>n−65−n</span>
<span><span><span>−<span>37n</span></span>−75</span>=<span>−65</span></span><span><span><span><span>−<span>37n</span></span>−75</span>+75</span>=<span><span>−65</span>+75</span></span><span><span>−<span>37n</span></span>=10</span><span><span><span>−<span>37n</span></span><span>−37</span></span>=<span>10<span>−37
</span></span></span><span>n= <span><span>−10/</span>37 <--------- answer</span></span>
Answer:
-18
Step-by-step explanation:
Let x be our number. First we have to write our equation.
The product of a number and -8 is represented as -8x (-8 multiplied by x). Remember that 'product' signifies multiplication.
The result is eight times the sum of x and 36. This is represented as 8(x + 36). We add x and 36 first because 8 has been multiplied by the sum of those two numbers.
So our equation is:
-8x = 8(x + 36)
We can now solve for x. First, expand the bracket.
-8x = 8x + 288
Next, subtract 8x from both sides. This will give us only one term containing x, which will make it easier to solve.
-8x - 8x = 8x + 288 - 8x
-16x = 288
Divide both sides by -16
x = -18
The choices are:
<span>A.
The student identified the greatest common factor incorrectly.
B.
The student incorrectly divided each term by the greatest common factor.
C.
The student failed to simplify the expression.
D.
The mathematical work shown is correct.</span>
I think the correct answer from the choices is option D. The mathematical work shown is correct. Hope this answers the question. Have a nice day.
Answer:
(4,4)
Step-by-step explanation:
y = 2x - 4 -------eqn 1
4y = x + 12 ------eqn 2
From eqn 1 y = 2x - 4; insert in eqn 2
4 (2x-4) = x + 12 (open the bracket)
8x - 16 = x + 12 (taking like figures to the same side, sign changes)
8x - x = 12 + 16
7x = 28
x = 28/7
x = 4
From eqn 1
y = 2x - 4
y = 2(4) - 4
y = 8 - 4
y = 4
(x,y) = (4,4)